Overview of systematic reviews on strategies to improve treatment initiation, adherence to antiretroviral therapy and retention in care for people living with HIV: part 1. Issue 9 (23rd September 2020) - Mbuagbaw, Lawrence; Hajizadeh, Anisa; Wang, Annie; Mertz, Dominik; Lawson, Daeria O; Smieja, Marek; Benoit, Anita C; Alvarez, Elizabeth; Puchalski Ritchie, Lisa; Rachlis, Beth; Logie, Carmen; Husbands, Winston; et al.
Abstract : Objectives: We sought to map the evidence and identify interventions that increase initiation of antiretroviral therapy, adherence to antiretroviral therapy and retention in care for people living with HIV at high risk for poor engagement in care. Methods: We conducted an overview of systematic reviews and sought for evidence on vulnerable populations (men who have sex with men (MSM), African, Caribbean and Black (ACB) people, sex workers (SWs), people who inject drugs (PWID) and indigenous people). We searched PubMed, Excerpta Medica dataBASE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Web of Science and the Cochrane Library in November 2018. We screened, extracted data and assessed methodological quality in duplicate and present a narrative synthesis. Results: We identified 2420 records of which only 98 systematic reviews were eligible. Overall, 65/98 (66.3%) were at low risk of bias. Systematic reviews focused on ACB (66/98; 67.3%), MSM (32/98; 32.7%), PWID (6/98; 6.1%), SWs and prisoners (both 4/98; 4.1%). Interventions were: mixed (37/98; 37.8%), digital (22/98; 22.4%), behavioural or educational (9/98; 9.2%), peer or community based (8/98; 8.2%), health system (7/98; 7.1%), medication modification (6/98; 6.1%), economic (4/98; 4.1%), pharmacy based (3/98; 3.1%) or task-shifting (2/98; 2.0%). Most of the reviews concluded that the interventions effective (69/98; 70.4%), 17.3% (17/98) were neutral or were indeterminate 12.2% (12/98). Knowledge gaps were the types of participants included in primary studies (vulnerable populations not included), poor research quality of primary studies and poorly tailored interventions (not designed for vulnerable populations). Digital, mixed and peer/community-based interventions were reported to be effective across the continuum of care. Conclusions: Interventions along the care cascade are mostly focused on adherence and do not sufficiently address all vulnerable populations.